Italy: Brain Drain or Brain Circulation? - Saint-Blancat, Chantal (International Higher Education, 2018)
Giving a Voice to Italian Scientists in Europe, a research project based on 83 in-depth interviews and a subsequent online survey, shows that transforming brain drain into brain circulation or into a potential scientific diaspora is not an easy task. Overturning Italy’s low level of investment in R&D and building reciprocal acknowledgment and trust between scientists abroad and in their country are identified as prerequisites for this transformation.